DEVELOPMENT AND EVALUATION OF BLOCKCHAIN-BASED E-LEARNING PLATFORMS TO IMPROVE DATA SECURITY - Guntur Arie Wibowo; Nukman; Arnes Yuli Vandika (CV. ADIBA AISHA AMIRA, 2023)
In the industrial era 4.0 with advances in technology and information, e- Learning refers more to distance learning-based learning involving internet networks. E-learning allows flexibility and effectiveness in the learning process. Even while the internet has made it possible to rapidly and readily find knowledge, there are still some things that could be harmful, such security flaws in e-learning platforms. Blockchain is a computer database that electronically saves data in an electronic manner. Blockchain technology has a big impact on data security and industry. Blockchain technology is a mechanism that makes it possible to validate digital transactions securely and decentralized. The literature study approach was used to conduct the research. The idea of e-learning and how it developed, data security issues in e-learning, the fundamentals of blockchain technology, the use of blockchain-based e-learning platforms, and an assessment of the effect of employing blockchain on data security are all covered in this study.